دور الموارد البشرية في تحقيق التنمية المستدامة - صالحي, ايمان (جامعة الوادي University of Eloued, 2017)
لقد برز مفهوم التنمية المستدامة على غرار تفاقم مشكلة التدهور البيئي وبداية اصطدام مطالب حماية البيئة بمطالب التنمية الاقتصادية فهي تعتبر إشباع احتياجات الحاضر دون تدمير قدرة الأجيال المقبلة على تلبية احتياجاتها الخاصة في إطار الحفاظ على الموارد الطبيعية وضرورة دمج الموارد البشرية في تحقيق التنمية المستدامة وتكمن أهمية هذه الدراسة في أن المورد البشري من خلال الاستغلال الفعال للمعارف والمهارات والسعي لتحقيق هذه العملية والهدف الأساسي من هذه الدراسة: هو دراسة مفهوم التنمية المستدامة كمفهوم جديد وشرح أبعادها وبمعناها الواسع ودور الموارد البشرية في تحقيقها، وكان الإشكالية الرئيسية كالتالي: إلى أي مدى تساهم الموارد البشرية في تحقيق التنمية المستدامة؟ وحاولنا الإجابة على الإشكالية من خلال الفرضية الرئيسية التالية: كلما زاد الاهتمام بالموارد البشرية أدى ذلك إلى تحقيق التنمية المستدامة. واعتمدنا في هذه الدراسة على المنهج الوصفي للوقوف على المفاهيم وعرض خصائصها ولدراسة هذا الموضوع قمنا بتقسيم الدراسة إلى ثلاثة فصول : الفصل الأول الذي تناولنا فيه تعريف الموارد البشرية وكانت لنا تغطية حول تعريف تخطيط الموارد البشرية وإبراز أهميته وأهم مراحله أما الفصل الثاني كان حول ماهية التنمية المستدامة من خلال السياق التاريخي لظهور هذا المفهوم وتعريفه وخصائصه وأهدافه وصولا إلى أبعاده، وفي الفصل الثالث تطرقنا إلى واقع الاهتمام بالموارد البشرية ودورها في التنمية المستدامة The concept of sustainable development, like the deterioration of the environmental degradation problem and the beginning of the collision of environmental protection demands with the demands of economic development, is considered satisfying the needs of the present without destroying the ability of future generations to meet their special needs in the context of natural resources conservation and the need to integrate human resources into sustainable development. To study the human resource through the effective exploitation of knowledge and skills and to pursue this process. The main objective of this study is to study the concept of sustainable development as a new concept and explain its dimensions, The main problem was: To what extent do human resources contribute to sustainable development? We tried to answer the problem by the following main premise: the more attention to human resources, the more sustainable development has been achieved. In this study we have adopted the descriptive approach to understanding the concepts and presenting their characteristics. To study this topic, we divided the study into three chapters: The first chapter dealt with the definition of human resources and we covered the definition of human resources planning and highlighted the importance and the most important stages. The second chapter was about the nature of sustainable development through the historical context of the emergence of this concept and its definition and characteristics and objectives to reach its dimensions. In Chapter III, Humanity and its role in sustainable development, where we reached the following results: Human resources are a component of sustainable development that has become a wealth in the era of globalization. The development of the human element is a means of achieving sustainable development. The development of the human element, its knowledge and skills is the most important resource and investment in the future.
سياسة عامة وادارة محلية
Keywords: الموارد البشرية - التنمية - التنمية المستدامة; Human Resources - Development - Sustainable Development